Evaluation of the flexural strength of cold-formed steel studs with embossed flanges - Reynolds, Kevin Brandt (Kansas State University, 2009)
Cold-formed steel studs, though they are a relatively new building material, have become a mainstay in modern construction. They are favored over traditional lumber studs for their high strength to weight ratio and resistance to insects and rot. Due to their relative newness as a material, new advances in their design and implementation are being developed quite rapidly. One such advancement is flange embossing, a technique used to increase the strength of the connection of screws into the studs. Currently, embossed flanges are not specifically addressed in the North American Specification for the Design of Cold-Formed Steel Structural Members (AISI S100), thereby preventing current design equations from being used to calculate an embossed stud's member properties. An experimental investigation was undertaken to determine what effect, if any, flange embossing has on the nominal flexural strength of cold-formed steel studs as determined using the provisions of AISI S100-07. Studs with embossed flanges were tested in bending and their actual flexural strength was computed. This data was then compared with the nominal flexural strength determined using the AISI Specification, without embossing, to determine if these equations would still be appropriate for the design of embossed studs.
Keywords: Cold-Formed Steel; Embossing; Engineering, Civil (0543)